Strategi Green Marketing Mix untuk Mewujudkan Green Brand Equity yang Baik dalam Pengembangan Usaha - Ferdinand Tri Angga Wardana; Muhammad Perdi; Ahmad Gusti Firmansyah; Akses Mardianto Siburian; Jerian Wilson Pekkei; Radithya Ozora; Freitty Zhinta Artika (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of the implementation of the green marketing mix in shaping green brand equity and its contribution to enhancing competitive advantage and business development amid increasing environmental awareness among society.This research employs a quantitative method using a survey technique through Likert-scale questionnaires distributed to 76 respondents, consisting of students, business actors, and consumers. The sampling technique used is purposive sampling. Data analysis is conducted using linear regression with the assistance of SPSS, complemented by validity testing and classical assumption tests.The results indicate that all components of the green marketing mix (product, price, promotion, and place/distribution) have a positive effect on green brand equity. The implementation of green marketing strategies is proven to enhance positive perceptions, trust, and customer loyalty, thereby strengthening the company’s competitive position.These findings can serve as a reference for business practitioners in consistently implementing environmentally-based marketing strategies to strengthen brand image, increase customer loyalty, and support sustainable business performance.This study contributes added value by linking the concepts of green marketing mix and green brand equity within the context of business development, particularly in markets that are increasingly concerned with environmental issues.